Favorable Outcomes After Liver Transplantation With Normothermic Regional Perfusion From Donors After Circulatory Death: A Single-center Experience. Issue 5 (May 2019) - Ruiz, Patricia; Gastaca, Mikel; Bustamante, Francisco Javier; Ventoso, Alberto; Palomares, Ibone; Prieto, Mikel; Fernández, Jose Ramón; Salvador, Patricia; Pijoan, Jose Ignacio; Valdivieso, Andres
Abstract : Background: Controlled donation after circulatory death (cDCD) has been associated with a high incidence of ischemic cholangiopathy and other perioperative complications. In an attempt to avoid these complications, we implemented an active protocol of cDCD liver transplant (LT) with normothermic regional perfusion (NRP) preservation. Methods: This is a descriptive analysis of data collected from a prospective date base of cDCD LT preserved with NRP from January 2015 to June 2017 with a minimum follow up of 9 months. Results: Fifty-seven potential cDCD donors were connected to the NRP system. Of these, 46 livers were transplanted over a 30-month period (80% liver recovery rate). The median posttransplant peak in alanine transaminase was 1136 U/L (220-6683 U/L). Seven (15%) patients presented postreperfusion syndrome and 11 (23%) showed early allograft dysfunction. No cases of ischemic cholangiopathy were diagnosed, and no graft loss was observed over a medium follow-up period of 19 months. Of note, 13 donors were older than 65 years, achieving comparable perioperative and midterm results to younger donors. Conclusions: As far as we know, this represents the largest published series of cDCD LT with NRP preservation. Our results demonstrate that cDCD liver grafts preserved with NRP appear far superior to those obtained by the conventional rapid recovery technique.